Respon Muhamamdiyah dalam Bidang Pendidikan (Study Kasus) di PCM Sei Rampah Kabupaten Serdang Bedagai - Sofi Ananda; Muhammad Ridho; Jamal Situmorang; Hasrian Rudi Setiawan (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
What is the formulation of the response of Muhammadiya in the education field? The purpose of this study was to study how Muhammadiyah's response in the field of education in Sei Rampah. This research is a qualitative research (Case Study) in the development of education in Sei Rampah. The method used in this study was conducted on research data. Data collection techniques presented consisted of observation techniques, interviews (interviews) and also documentation. The data analysis phase used is data reduction, data presentation, and data verification. The results of this Research Development (Case Study) were a design carried out to determine PCM Sei Rampah's responses in the field of education. The subjects of this study were the Muhammadiyah Branch Chairperson, the Dikdasmen Council, and the school. The implementation can be done well, so it can be learned about the development of education in Sei Rampah